The Journey of the Prophet Musa, peace be Upon him, with the Righteous Worshipper - an Intentional Study - Abdel-Jabbar , Mahmoud (Islamic Sciences Journal, 2023)
ABSTRACT Surat Al-Kahf is one of the surahs of the Qur’an, which contains great stories and contains wisdom, sermons, and lessons. This surah has served by scholars and students of knowledge from various backgrounds, because it is abundant in arts. So I wanted to shed light on an aspect of these stories in order to address it both in terms of intentions and skills, so I chose the journey of our master Musa, peace be upon him for the most prominent aspect of the intentions in the story and its three events represented in the breach of the ship, the killing of the boy, the building of the wall, and how the righteous worshipper balanced between the evils that occurred to choose the lightest of them to commit in order to avoid the greater evil.